Photosensitizer-free visible-light-mediated gold-catalyzed 1,2-difunctionalization of alkynes - Huang, Long; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2016)
Under visible-light irradiation, the gold-catalyzed intermolecular difunctionalization of alkynes with aryl diazonium salts in methanol affords a variety of α-aryl ketones in moderate to good yields. In contrast to previous reports on gold-catalyzed reactions that involve redox cycles, no external oxidants or photosensitizers are required. The reaction proceeds smoothly under mild reaction conditions and shows broad functional-group tolerance. Further applications of this method demonstrate the general applicability of the arylation of a vinyl gold intermediate instead of the commonly used protodemetalation step. This step provides facile access to functionalized products in one-pot processes. With a P,N-bidentate ligand, a stable aryl gold(III) species was obtained, which constitutes the first direct experimental evidence for the commonly postulated direct oxidative addition of an aryl diazonium salt to a pyridine phosphine gold(I) complex.
Gesehen am 29.09.2017